Field notes contributed by Dennis L. Carter, November 30, 1998 - Carter, Dennis L.et al (1998)
Fall report of birds found in northeast Iowa contributed by Dennis L. Carter. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1998. Epson - sheet feed/flatbed